The interplay of Students’ Habit On Watching English Movie And Listening In Toefl Test - Tut Wuri Handayani; Baso Jabu; Nur Aeni (Eduvelop: Journal of English Education and Development, 2024)
The habit of watching English movies provides an opportunity to learn language skills. Movies can be difficult for students to understand because they speak more quickly than they do in everyday conversation or English, but they can also be entertaining and help to improve specific English language skills, like listening. To measure English language skills, especially listening, reading, and structure, the English language test or TOEFL has recently become a very important thing to master in facing global competition and has become a prerequisite for graduation on various campuses in Indonesia. The study aimed to determine whether students' habits of watching English-language films and their listening comprehension on the TOEFL were related. The students were members of the English Education Department at UIN Alauddin Makassar.The study design used a quantitative approach and the correlation method. The researcher employed tests and questionnaires to gather data. The study's participants consisted of third-semester English Education Department students at UIN Alauddin Makassar. There were one hundred students in the study's sample. Random sampling was used for this study.The method of using a questionnaire to gather information about students' viewing habits of English-language films. The TOEFL exam was the method used to gather listening data. This data analysis method made use of the Pearson product-moment correlation. The results of the study indicate a significant positive correlation (rxy = 0.826 > rtable = 0.196) between students' listening and watching habits in English during the TOEFL exam at UIN Alauddin Makassar. As a result, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. This statement indicates that there is a positive and significant relationship between students' habit of watching English-language movies and their ability to listen on the TOEFL exam.